Validating sociotechnical systems' requirements through immersion - Gregoriades, Andreas; Pampaka, Maria (My University, 2016)
One of the most critical phases in complex socio-technical system development is the validation of nonfunctional requirements (NFR). During this phase, system designers need to verify that the proposed system's NFRs will be satisfied. A special type of NFRs which is often ignored regards the Human Factors (HF) NFRs. These requirements are of vital importance to socio-technical systems since they affect the safety and reliability of human agents within such systems. This paper presents a scenario-based approach for validating HF NFRs using VR CAVE simulation. A case study is used to demonstrate the application of the method in the validation of the situation awareness NFR of an in-vehicle Smart driver assistive technology (SDAT). Such systems aim to alleviate accident risks by improving the driver's situation awareness by drawing their attention on critical information cues that improve decision making. The assessment of the HF NFR is achieved through an experiment with users in a virtual environment. This work describes and demonstrates a method that utilizes a custom-made, modular 3D simulator that uses a number of hazardous scenarios, for the validation of the HF NFRs of prospective systems.
Keywords: Human Factors; Requirements validation; Simulation; Virtual reality